Sacred natural sites in the face of global changes: the case of Mount Kinabalu in Malaysian Borneo / Christy Bidder - Bidder, Christy (Universiti Teknologi MARA, Perak, 2023)
Many indigenous communities worldwide assign special recognition to natural places and designate them sacred sites. There are various reasons for the sacredness of natural sites, including places where deities and ancestral spirits reside, where physical and non-physical healings can occur, where humankind can contact the spiritual entity, and where revelation and transformation can occur. However, many sacred natural sites are susceptible to threats, particularly those related to modernization and globalization. Based on this background, this study sought to examine the status of the sacredness of Mount Kinabalu within the context of global changes by analysing the traditional cultural and spiritual values of the indigenous Dusun community. Specifically, it attempted to answer two research questions: Is Mount Kinabalu still considered a sacred mountain by the Dusun community today? How have modernization and globalization impacted the sacredness of Mount Kinabalu? The study compared the older and the younger Dusun in their responses to gain deeper insights into these questions. The study employed a quantitative, cross-sectional design. It used questionnaires to collect data from the Dusun living in two principal villages at the foot of Mount Kinabalu. Data from 381 completed questionnaires were analyzed using percentages and mean scores. The key results showed a decline in traditional cultural and spiritual values among the younger Dusun, which might further mean they no longer ascribed a spiritual significance to Mount Kinabalu as the older Dusun did. The decline could negatively impact biodiversity conservation and the community's ethnic identity, lifestyles, and rights. The study concluded with a suggestion for responses to the change.